(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
A number of examinations identified variables which proved to help or even obstruct the optimal progress, including personality and cognitive development. By exploring the risk and protective factors in a family our aim was to establish the level of presence of risk factors influencing the development of the child between 0 and 7 in the families. To verify the connection between the variables we applied mathematical and statistical methods. Regression models were utilized for examining the statistical significance of the direct and the indirect impact of variables which proved to be differentiating factors. Our analysis showed that in many cases risk factors influencing the development of the child occursimultaneously and they strengthen the possibility of an unfavourable development and increase the risk of falling behind.